SEJARAH PERKEMBANGAN ISLAM DI KECAMATAN TOMBATU TAHUN 1952-2010 - Gosal, Nofi (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
This thesis focused on research on how the entry of Islam in sub-Tombatu. To do a research, researcher must use the method as usually used in writing history, consist of four, which are: heuristic, criticsm analysis, interpretation, and historiography. In this research, the writer present some basic, for example: how is the process of arrival and development of religion of Islam population as well as its influence in the middle of community of Tombatu since 1952-2010. Start from the problem above a writer can conclude that the process of the entry of Islam in sub-Tombatu never be separated from the process of the entry of Islam in Indonesia. The influence of Islamic teachings in Tombatu came from several region on Indonesia such as Bolaang Mongondow, Gorontalo, Sanger Talaud, Mollucas, South Sulawesi, Makassar, and Tondano which is a descendant of freedom fighters who was exiled in North Sulawesi. Besides, the entry of Islam was bring by the traders of Arabian who came from Java and Kalimantan. They came to Tombatu with purpose of trade, but also they did the atraction of traditional madicine at once spread Islam by stories and lectures. Until one day began to pass the development of religion Islam through the marriage as well as the start to create an exchange of customs and culture with a native of Tombatu. Key word : Development, religion, social.